Geosocial networking mobile applications use and HIV and other sexually transmitted infections among men who have sex with men in Southern China: A cross-sectional study - Guo, Zhihui; Feng, Anping; Zhou, Yiguo; Gao, Yanxiao; Sun, Yinghui; Chen, Yuanyi; Zhou, Xinyi; Zou, Huachun (Frontiers in Public Health, 2023)
Introduction Men who have sex with men (MSM) are increasingly using geosocial networking (GSN) mobile applications (apps) to socialize in the community. Our study aimed to compare sexual behaviors between app-using MSM (app users) and non-app-using MSM (non-app users), and evaluate the association between app use and sexually transmitted infections (STIs). Methods Eligible MSM were recruited from January to August 2017 in three metropolitan cities: Guangzhou, Shenzhen and Wuxi. A self-completed tablet-based questionnaire was collected about socio-demographic characteristics, sexual behaviors and app use. Blood samples were collected to test for HIV and syphilis. Rectal swabs and urine samples were collected to test for gonorrhea and chlamydia. Anogenital warts were checked by clinicians. Chi square tests and logistic regression were used to compare the prevalence of STIs and the characteristics between app users and non-app users. Results A total of 572 MSM were included in our analysis. The majority of participants were 20 to 29 years old (61.7%). 89.0% of MSM had ever used at least one GSN app, and 63.8% MSM had anal intercourse (AI) partners found via apps. Compared with non-app users, app users were more likely to have higher education level (adjusted OR (AOR) 3.36, 95% confidence interval (CI) 1.65-7.03), have regular sex partners (2.40, 1.16-5.19), have two or more casual sex partners (2-5: 2.90, 1.21-6.90; ≥6: 13.91, 3.13-82.90), have condomless anal intercourse (CAI) with casual sex partners in the past six months (2.50, 1.28-5.04), do not know their last sex partner’s HIV status (2.16, 1.13-4.21), have tested for HIV in the past year (2.09, 1.07-4.09). Prevalence of HIV (8.3% vs 7.9%, P=.93), syphilis (6.9% vs 11.1%, P=.34), gonorrhea (5.1% vs 6.3%, P=.90), chlamydia (18.5% vs 12.7%, P=.36), and anogenital warts (4.9% vs 4.8%, P=1.00) were similar between app users and non-app users. Conclusions GSN app users were more likely to have high-risk sexual behaviors, but the prevalence of HIV and other STIs were similar to non-app users. Longitudinal studies comparing the incidence of HIV/STIs between long-term app users and non app users may be necessary to clarify the impact of app use on HIV/STIs risk.